Effect of Ashitaba Extract on Cholesterol in Wistar Rats given a high-fat diet and computational lethal dose test - Widyaningsih, Indah; Sugiharto, Natsya Nurulita; Rahmawati, Febtarini; Amma, Fuad; Simamora, Dorta (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
High levels of cholesterol in the blood can cause various health problems, namely atherosclerosis, stroke, coronary heart disease, to hypertension. One drug option for someone with hypercholesterolemia is simvastatin. In addition to the use of the drug simvastatin, can take medicinal plants. A medicinal plant that can help lower high cholesterol levels is Ashitaba leaf extract (Angelica keiskei). One of the ingredients in ashitaba extract is xanthoangelol E, Ashitaba chalcones, which can reduce cholesterol synthesis. The purpose of this study was to determine the effect of ashitaba extract (Angelica keiskei) on the cholesterol levels of Wistar rats (Rattus novergiccus) given a high-fat diet. In this study, a computational lethal dose test was also carried out. The population in this study was male white rats of the Wistar strain with samples taken from as many as 30 heads. Data analysis of this study used the One Way Anova statistical test. The results showed that giving ashitaba extract 150mg/kg body weight, 300mg/kg body weight, and 600mg/kg body weight did not affect the cholesterol levels of Wistar rats given a high-fat diet. This is proven by the results of the ANOVA test obtained a significance value of 0.761 > 0.05. Research on the toxic effects of ashitaba extract needs to be done for further research.